Bifunctional additive phenolic acids grafted ethylene-vinyl acetate copolymers for improving the cold flow properties and oxidative stability of waste cooking oil biodiesel-diesel blends. (15th January 2023) - Sun, Bin; Zhang, Xiaokang; Zhao, Yuzhuang; Chen, Fengfei; Ren, Feihe; Lin, Hualin; Xue, Yuan; Han, Sheng
Highlights: Two types phenolic acids were grafted on the ethylene–vinyl acetate (EVA) copolymers with different VA contents to improve the cold flow properties (CFPs) and oxidative stability (OS) of B20. Bio-based GA-grafted EVA showed better improvement effects than that of commercial DTBHA. EVA-GA-2 exhibited better effects on the CFPs and OS at 0.1 wt% dosage, and the cloud point (CP), pour point (PP), and cold filter plugging point (CFPP) reduced by 5 °C, 10 °C, and 11 °C, respectively. The induction period (IP) increased from 1.66 h to 25.56 h. The possible action effects of improving CFPs and OS were discussed. Abstract: Poor cold flow properties (CFPs) and oxidative stability (OS) are the main commercial obstacles affecting the application of biodiesel. Most additives only improve a single specific property. In this study, a bifunctional additive was prepared to improve the CFPs and OS of waste cooking oil (WCO) biodiesel blends. 3, 5-di- tert -butyl-4-hydroxybenzoic acid (DTBHA) and gallic acid (GA) were grafted on the ethylene–vinyl acetate (EVA) copolymers with different VA contents, and the grafted EVAs were used as the cold flow improvers and antioxidants for B20 (20 vol% WCO biodiesel + 80 vol% diesel fuel). EVA with 25 % VA content (EVA-2) at 0.15 wt% dosage exhibited better reduction on cloud point (CP), pour point (PP), and cold filter plugging point (CFPP) by 5 °C, 7 °C, and 10 °C, respectively. The EVA had depression effects on the CFPs of B20, whereas it had no effects on OS. The EVA presented further improvement on the CFPs and OS of B20 after the grafting of phenolic acids. Bio-based GA-grafted EVA showed better improvement effects than that of commercial DTBHA. EVA-GA-2 exhibited better effects on the CFPs and OS at an optimal dosage of 0.1 wt%, and the CP, PP, and CFPP reduced by 5 °C, 10 °C, and 11 °C, respectively. The induction period increased from 1.66 h to 25.56 h. The effects of the bifunctional additive on CFPs and OS of B20 were discussed.